Designing displays for older adults - Pak, Richard; McLaughlin, Anne (Human factors and aging series, 2011)
A primer on age-related changes in cognition, perception, and behavior organized into meaningful principles that improve understanding. It explores the complex set of mental and physical changes that occur during aging and that can affect technology acceptance, adoption, interaction, safety, and satisfaction